Characterization of Trichoderma species isolated from soil and efficacy Of Trichoderma asperellum as biocontrol agent of fusarium wilt disease of banana - Syd Abdul Rahman, Sharifah Siti Maryam (2018)
Chemical pesticides are commonly used for managing Fusarium wilt disease of banana that is caused by Fusarium oxysporum f. sp. cubense. However, the uses of chemical will lead to environmental disruptions and are ineffective in some conditions and disease stage. In order to initiate of application of an ecofriendly cure of the disease, this study was focused on biological control agent against the pathogen of Fusarium wilt of banana. Trichoderma species is one of the microorganisms which having antagonistic properties. The objectives of this study are to isolate and identify Trichoderma species isolated from various soil samples using phenotypic and molecular characterization, to screen antagonistic Trichoderma species against pathogen of Fusarium wilt disease under in-vitro condition, and to examine the efficacy of Trichoderma asperellum as a biocontrol agent of Fusarium wilt disease of banana under plant house condition. The soil samples were collected around eleven sites from different states of Malaysia and sixty-nine of the fungal isolates were obtained from Laboratory of Mycology, Department of Biology, Faculty of Science, UPM. The fungal isolation was completed using soil dilution technique and cultured on Rose Bengal Agar (RBA) to obtain a single colony-forming unit (CFU). The CFU was transferred onto Potato Dextrose Agar (PDA) and identification was carried out based on phenotypic and molecular characterization. About 326 isolates were classified into eight Trichoderma species, which are Trichoderma asperellum, T. hamatum, T. harzianum, T. koningiopsis, Hypocrea rodmanii, T. spirale, T. viride and T. virens. All the isolates were further used for in vitro study, the finding showed three high percentage inhibition of radial growth (PIRG) were observed in dual culture plates of Trichoderma isolates B1902 (84.85%), T2007 (77.78%) and C1667 (75.76%) were selected and further used for in vivo study. Based on morphological, internal transcribed spacers (ITS) and translation elongation factor 1 alpha (TEF-1α) sequences analysis, those three selected isolates were identified as T. asperellum. In plant house condition, T. asperellum B1902, T2007, and C1667 were successfully inhibited the growth of Fusarium oxysporum f. sp. cubense isolate 9888 at 10 weeks and 20 weeks after inoculation. The best candidate was T. asperellum B1902 with Disease Severity Index (DSI) value of 0.2 compared to the inoculated control with DSI at 3.6. As a conclusion, T. asperellum can be used as an alternative treatment in managing Fusarium wilt disease. Hence, the future study should be focusing more in applying T. asperellum as biological agent in the field and controlling other plant diseases in agricultural plantation.